Banco comunitário no Preventório: uma experiência de economia solidária - Ferreira, Marcos Rodrigo Maciel (2018)
This article offers a study about the contribution of the Community Bank of Preventório, in Niterói, Rio de Janeiro, for local development. Community Development Banks (BCDs) are organizations of solidary finance that operate in territories with socioeconomic vulnerabilities, with the mission to organize the local economy and to strengthen the community organization through the provision of financial services, such as microcredit, as well as banking and advisory services to enterprises, among other actions. In two decades, about one hundred BCDs were opened in several places in the country, those were organized in the Brazilian Network of Community Banks. These experiences are based on the methodology of Palmas's Bank, in Fortaleza, Ceará, which nationally and internationally are an integral part of the segment called solidary finance. We chose as method of scientific research the study case. We did this because we are studying an experience that develops in the Preventório Community, a community association called Banco do Preventório, which works on the local development. It's an organization in full operation, where a structure of discussion can be regulated, but isolation and laboratory control can not be done. It's a research about social, cultural and political context in movement. The focus of this study is to understand the implementation process and the development of BCD of Preventório's activities, and specificities of the Bank in relation with the territory in order to understand the organization's contribution to local development. Finally, we conclude that the Bank contributed to local development and we identified several processes that led to this. However, the development that the Bank generated was related to the citizenship. Although the Bank has sought development from financial services (microcredits, social money, etc), it was important the action to mobilize local factors, that worked together in various projects and actions, as civil society, the local market and public power, including.